Bella Poldark : a novel of Cornwall, 1818-1820 - Graham, Winston (Poldark series, 2019)
"The twelfth book in Winston Graham's classic Poldark saga, now a major TV series from Masterpiece PBS. Cornwall 1818 We continue the tale of Ross and Demelza; of the wayward Valentine Warleggan, whose existence keeps open the old wounds of the feud between Ross and George; of Bella, the Poldarks' youngest daughter, whose precocious talent as a singer is encouraged by her old flame, Christopher Havergal, and by a distinguished French conductor, who has more in mind than Bella's music; of Clowance, the Poldarks' widowed daughter, who considers remarriage to one of two rival suitors; and of a murderer who stalks the villages of west Cornwall. In his Poldark series, Winston Graham explores the complications of love lost and the class struggle of early 19th-century England with a light comic touch. Bella Poldark is the final Poldark book"--